Retrofit for purpose : low energy renewal of non-domestic buildings - Prasad, Sunand (RIBA Publishing, 2014)
This book examines a range of state-of-the-art non-domestic retrofit projects. Its chapters explore common challenges, offer practical solutions and provide a clarion-call to architects and clients for better, smarter retrofit. Twelve case studies focus as much on the transformation of usability and image as on the improvements in the energy and resource use of non-domestic buildings. While an essay section places these projects into a wider context, suggesting that despite the importance of sharing and analysing data, there is more to retrofit than just energy efficiency. The authors take a range of other retrofit variables: from client ambition to tenure, budget, use type, age, context, fashion and fiscal arrangements and assess how retrofit can be made affordable, how it fits in with wider government policy and how performance can be measured.